Elementy uzbrojenia na kaflach renesansowych z założeń dworskich w Kozłowie - Zdaniewicz, Radosław (Acta Universitatis Lodziensis. Folia Archaeologica, 2012)
During archaeological excavations conducted on the site of the relics of manor houses in Kozłów, Silesia province, an impressive set of stove tiles has been discovered. Some of the tiles’ facings were decorated with representations that are interesting iconographic sources for the study of early medieval arms. The first tile was discovered in the remains of the manor from the late 15th and 16th c. Facing of this tile is decorated with a side profile of the rider’s head in a closed helmet with a crest. Visual presentation is not so detailed and not all the details of surface texture are sharp. The portrayed helmet is probably a tournament example called the frog face helm. Its bell is crowned with an extensive crest, which is an oval with short and long feathers modeled in different directions. At the back of the bell there are ribbon like mantlings visible. Due to the lack of large part of the tile it is difficult to determine whether the visible crested helm was a part of a heraldic motif or whether it was connected with representations of knightly culture such as tournament scenes for example. The first possibility seems more likely. The second tile was found in layers associated with the manor which functioned in the 16th century. The presentation on the facing of tile refers to a series of woodcuttings created by the German renaissance painter Georg Pencz, gathered under one title of Twelve Heroes of the Old Testament. These works were inspired by the text of the poem by Hans Sachs from 1531. The author was glorifying the heroic exploits of the twelve heroes from the Old Testament: Joshua, Gideon, Jephthah, Samson, Jonathan, David, Abia, Azah, Josaphat, Amazia, Hezekiah and Judas Maccabeus, portraying them as symbols of the defenders of Christianity. Facing of the tile from Kozłów is ornamented with the image of Juda’s king Amazia. Similar to a Pencz’s graphic, he has been presented in an armour with his head and torso slightly turned to the left. The whole scene was made with high attention to the details, which allows us to make some valuable observations on the components of the armour. The helm is a close helmet with bevor and gorget, depicted with a lifted visor. The torso is protected with a bulging breastplate with fauld attached below. The arm is covered with a massive overlapping breastplate pauldrons and bulging rerebrace. In the lower part, at the height of faulds, there is a visible fragment of a sword hilt, one and a half or two-handed, topped with an oval pommel. A similar suit of armour, often called Maximilian armour, was used in Europe since the 1630s. Armour of this type was popular at that time in Silesia as well, what is indicated by the numerous tombstone representations.